Identifying Areas of High Gold Potential Using Geochemical Prospecting Methods: The Tenado Area in the Boromo Birimian Belt, West-Central Burkina Faso, West Africa - Aziz Fayçal Tarnagda; Pascal Ouiya; Saga Sawadogo (European Scientific Journal, ESJ, 2024)
The investigation area is located in the central-western region of Burkina Faso, in a geological environment that incorporates the Paleoproterozoic formations of the Boromo greenstone belt. This zone already has several gold showings and an active zinc mine, but no major gold deposits. The aim of this study is to define target areas with high gold potential for further prospecting. To meet this objective, we mainly used total rock geochemistry and stream sediment geochemistry methods. The combination of stream sediment gold content and litho-geochemical data has enabled us to highlight two areas of gold (Au) and various metal anomalies. The gold content of stream sediments is mainly influenced by that of the parent rock from which they are derived. In fact, strong gold anomalies are more common in clay sediments than in sandy sediments. These clay sediments are derived from basic rocks (basalt) and intermediate rocks (andesite-dacite), while the gold-poor sandy sediments are derived from granitoids. Basic to intermediate rocks are fertile for primary gold. Anomaly zone one (01) in the northern part of the study area (Kelsio, Zoula, Poa and Dyoro) and anomaly zone two (02) in the southern part of the study area (Kwademan, Baguiomo, Bérédo, Bonga and Baganapou) show occurrences of mainly gold and various metals (Zn, Cu, Ni).